Preparation of mesoporous titania xerogels under controlled synthesis conditions. Effects of processing in the textural, adsorption and photocatalytic properties - Marco Brown, José Luis; Blesa, Miguel Angel; Soler Illia, Galo Juan de Avila Arturo (Elsevier Science, 2017)
Fil: Marco Brown, José Luis. Comisión Nacional de Energía Atómica. Gerencia del Área de Seguridad Nuclear y Ambiente. Gerencia de Química (CAC); Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de San Martín. Instituto de Investigación e Ingeniería Ambiental; Argentina